Questions & answers - Foster, Nigel G. (Oxford University Press, 2007)
Oup's "Law Questions and Answers" series gives students the opportunity to practise their exam techniques and evaluate and assess their progress. The ideal revision aid, this new edition of "Q&A EU Law" is divided into chapters covering each major topic, and contains around fifty questions and answers designed to test even the best prepared student. The book opens with an introductory chapter providing guidance on study and examination skills, as well as an overview of EU and EC Law. Thereafter, each chapter contains an introduction focusing on important legal aspects and points of interest for each topic. After each question there is a commentary which highlights the essential elements of each question, followed by an answer plan providing a summary of key points. "Q&A EU Law" ends with a chapter of 'mixed subject questions' which will provide the perfect dry run at an examination. Nigel Foster is renowned as an author of clear, student-focused, high-quality textbooks. He is very much in touch with students' needs, as well as knowing exactly what the examiners are looking for. "Q&A EU Law" is accompanied by an Online Resource Centre providing annotated web links and a glossary of terms from the Dictionary of Law